Monitoring the Air Pollution and Evaluation of the Impact of Aluminium Production in Talco - RASULOV, Oqil; SCHWARZ, Marian (Journal of Environmental Management and Tourism, 2016)
The study was conducted in the aluminium plant TALCO (Tajik Aluminium Company). The objective was to evaluate the concentration of harmful substances (in particular hydrogen fluoride, fluorine salts, and sulphur dioxide) in the air. Data were collected within 0, 1, 5, 10, and 12 km from the plant emission source. The concentration of hydrogen fluoride ranged from 0.0043 to 0.0037 mg. m-3 and fluorine salts from 0.58 to 0.002 mg. m-3. The highest concentration of fluoride was found between 7 and 8 workshops, which were under the maximum allowable concentration (MAC). Within 1 kilometre from the plant, content of the substances is at a maximum and the minimum is already within 5th kilometre from plant borders. The concentration of all substances sharply decreased within 1 km from the plant.
Keywords: environmental monitoring; air pollution; fluoride; TALCO